MANAJEMEN LEMBAGA SEMI OTONOM (LSO) PENDIDIKAN YAYASAN WIHDATUL UMMAH BATUSANGKAR DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SDIT QURRATA A’YUN BATUSANGKAR - Miftah Novi. T (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This study was qualitative and focused on the management of Semi Autonomous Institute (LSO) Wihdatul Ummah Batusangkar Foundation of Education in Improving the Quality of Education in SDIT Qurrata A’yun Batusangkar. The background of this research was the parents are more interested to educate their children in Islamic Elementary School (SDIT) Qurrata A’yun, meanwhile half of them are teachers in SD, SMP, MTs, SMA, MA and lecturer. The result revealed that the management of Semi Autonomous Institute was run well. LSO did the management based on the guide book The Management System of Semi Autonomous Institute 2013. LSO organized the program to upgrade the quality of education in every units. The programs were 1) Early Years Program; 2) Monthly Activity; 3) Weekly Activity; and 4) Daily Activity. Then organized the budget, developed facility and did monitoring and controlling.Keywords: Management, Semi Autonomous Institute, Wihdatul Ummah Batusangkar Foundation, The Quality of Education